Entrepreneurial Orientation, Dynamic Capability and Innovation: The Effect on The Performance of MSMEs - Angga Lesmana; Nursantri Yanti; Marliyah Marliyah (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
Investigating how innovation, dynamic capabilities, and entrepreneurial orientation affect the performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan City is the objective of this study. The background of this study is based on the significant role of MSMEs in the Indonesian economy, but many still face challenges in maintaining competitiveness amid technological developments and market dynamics. This study uses quantitative methodology and survey techniques, with questionnaires distributed to MSMEs in Medan City. The impact of independent factors on MSME performance is analyzed using multiple linear regression. The findings show that innovation, dynamic capacity, and entrepreneurial mindset have a significant and positive impact on MSME success. These results highlight the importance of developing entrepreneurial traits, flexibility, and product or service innovation to improve the success of MSMEs. This study is designed to be a resource for business leaders and policymakers in developing more successful MSME development strategies.Keywords: entrepreneurial orientation, dynamic capabilities, innovation, MSME performance, economic uncertainty